Implementation Of Human Resources Strategy At PT Pos Tanjungpinang - Gusmatumi Gusmatumi; Salman Afdhal; Satriadi Satriadi; Elvi Lastriani (Pusat Riset dan Inovasi Nasional, 2023)
The Post Office has become an integral part of the communication and distribution system of correspondence in many countries around the world. However, with the rapid development of digital technology, the Post Office is facing new challenges to adapt to this change. This study aims to describe the role and transformation of the Post Office in facing the digital era.